Secularism out of its place - Paul R. Brass (Contributions to Indian Sociology 1998; 32; 485, 1998)
A major source of the problems in recent discussions of the continued relevance to contemporary Indian political life of the secular state and the practices associated with secularism lies in the heavy burden that has been placed upon these terms. Secularism, properly speaking, is an orientation and a set of practices. However, in India, it has become an ideology seen as both contesting with Hindu communalism by those who uphold it, and as contesting against the faith of the Indian peoples by those who lately stand against it. Secularism as an orientation and a set of practices is indispensable to India's future as a liberal democracy. However, it loses its force as a binding principle of Indian unity if it is transformed into an ideology.